Adherence to a healthy lifestyle and multiple sclerosis: a case–control study from the UK Biobank. (3rd June 2022) - Veronese, Nicola; Yang, Lin; Piccio, Laura; Smith, Lee; Firth, Joseph; Marx, Wolfgang; Giannelli, Gianluigi; Caruso, Maria Gabriella; Cisternino, Anna Maria; Notarnicola, Maria; Donghia, Rossella; Barbagallo, Mario; et al.
ABSTRACT : Background: Multiple sclerosis (MS) is a common and disabling condition. The importance of healthy lifestyle for this disease is poorly explored. Objective: To test whether adherence to healthier lifestyle patterns is associated with a lower presence of multiple sclerosis (MS). Methods: By using a case–control design, we investigated the combined association of four healthy lifestyle-related factors (no current smoking, healthy diet, exercising regularly, body mass index <30 kg/m 2 ) and the prevalence of MS. A logistic regression analysis, adjusted for potential confounders, was used and data reported as odds ratios (ORs) with their 95% confidence intervals (CIs). Results: 728 participants with MS were matched with healthy controls ( n  = 2, 912) using a propensity score approach. In a multivariable analysis, compared to those who scored low in the composite lifestyle score (0–1 healthy lifestyle factors), people who adopted all four low risk lifestyle factors showed a 71% lower odds of having MS ( OR  = 0.29; 95% CI: 0.15–0.56). Moreover, there was a strong linear trend, suggesting that the higher number of healthy lifestyle behaviors was associated with lower odds of having MS. Conclusion: Following a healthy lifestyle is associated with a lower prevalence of MS. This association should be explored further in cohort studies.